Tren Dan Dinamika Penelitian Akuntansi Syariah Di Indonesia: Analisis Bibliometrik - Dita Fauziah; Ai Nur Bayinah; Sepky Mardian; Fahma Rianti (Jurnal Akuntansi dan Keuangan Islam, 2022)
This study aims to look at trends, research dynamics and citation analysis of Islamic accounting articles published in nationally accredited accounting journals indexed by the Science and Technology Index (Sinta) during 2015-2019. The type of data used in this study is secondary data in the form of sharia accounting research papers that have been published online in national accounting journals indexed by Sinta. The method used in this research is bibliometric analysis using VOSViewer as an analysis tool. The result of the study show that the most researched topics of Islamic accounting are Islamic Bank, Islamic Social Reporting (ISR), Corporate Social Responsibility (CSR), Profitability, and Good Corporate Governance (GCG). The dynamics of this research fluctuated in the range of an average of 50 articles per year, but there was no significant increase or decrease. Then the literature most cited by Islamic accounting research articles is in the form of journal articles and books. There are 620 articles and 497 books respectively.Penelitian ini bertujuan untuk melihat tren, dinamika penelitian dan analisis kutipan artikel akuntansi syariah yang diterbitkan pada jurnal akuntansi terakreditasi nasional yang terindeks Science and Technology Index (Sinta) selama 2015-2019. Jenis data yang digunakan dalam penelitian ini adalah data sekunder berupa penelitian akuntansi syariah yang telah dipublikasikan secara online di jurnal akuntansi nasional yang terindeks Sinta. Metode yang digunakan dalam penelitian ini adalah analisis bibliometrik dengan menggunakan VOSViewer sebagai alat analisis. Hasil penelitian menunjukkan bahwa topik akuntansi syariah yang paling banyak diteliti adalah Islamic bank, Islamic Social Reporting (ISR), Corporate Social Responsibility (CSR), profitabilitas, dan Good Corporate Governance (GCG). Dinamika penelitian ini fluktuatif dalam kisaran rata-rata 50 artikel per tahun, tetapi tidak ada peningkatan atau penurunan yang signifikan. Kemudian literatur yang paling banyak dikutip oleh artikel penelitian akuntansi syariah adalah artikel jurnal dan buku. Masing-masing berjumlah 620 artikel dan 497 buku.